TEACHER AND STUDENT COMMUNICATION STRATEGY IN THE ONLINE LEARNING PROCESS AT SMA NEGERI 10 AMBON - Rido D Latuheru; Marleen Muskita (Universitas Gunadarma, 2022)
Communication activities are inherent in daily human life in socializing. The skill to communicate properly and correctly is a competency that a teacher must recognize. It is as stated in the Law of the Republic of Indonesia Number 14 of 2005, regarding Teachers and Lecturers, Government Regulation Number 19 of 2005, the issue of national education standards, and regulations Minister of National Education (Permendiknas) Number 16 of 2007 issues Standards for Academic Qualifications and Teacher Competency. This study aimed to find out the strategies used by teachers and students in the online learning process during the pandemic at SMA Negeri 10 Ambon. The type of research used is quantitative research. The location of this research was conducted at SMA Negeri 10 Ambon, with the consideration that there is an online teaching and learning process. The results obtained, testing the hypothesis that has been done hypothesis is accepted. It shows that teacher and student communication strategies have a significant influence on online learning at SMA Negeri 10 Ambon. The influence of teacher and student communication strategies on online learning at SMA Negeri 10 Ambon can be seen from the value of the coefficient of determination (R²). Based on the calculations, an R² value of 61.2% was obtained. Teacher and student communication strategies for online learning at SMA Negeri 10 Ambon, while the remaining 38.8% was explained or influenced by other variables not examined.